TECHNICAL AND TACTICAL TRAINING MODEL FOR GRECO-ROMAN WRESTLING - Novakovsky, S.V.; Maksimovich, V.A.; Rudenik, V.V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to develop a technical and tactical training model for Greco-Roman wrestling sport based on the modern sports training theory. Methods and structure of the study. Methodologically, the study was designed based on the P.K. Anokhin’s functional systems theory; N.A. Bernstein’s leveled movement construction concept; activity theory developed by psychologists L.S. Vygotsky, S.L. Rubinstein and A.N. Leontiev; the M.M. Bogen’s planned/ staged motor actions formation theory, etc. Results and conclusion. Technical and tactical training may be defined as the motor skill training and practical motor skill application tactics learning system for competitive progress. We developed, based on the sound theoretical provisions, the technical and tactical training model for Greco-Roman wrestling sport as a harmonized staged system designed to master motor skills on a situation-specific, proactive and creative basis – first in the eased modeled conditions; second in the focused motor skill trainings to effectively use the basic well-trained motor skill toolkit in competitive bouts; third, in the focused-creative motor skill trainings to make the athlete fit for finding best solutions under time pressure in every known motor situation; and fourth, in the creative motor skill / motor actions trainings to help find the best solutions of motor tasks in the unknown motor situations. The technical and tactical training model is recommended for practical application in wrestling sports as it was proved beneficial for the training service quality.